Examining Women’s support for birth encouragement policies in China: an extension of the influence of presumed media influence model - Li, Shiyao (Frontiers in Psychology, 2024)
This study employs the influence of the presumed media influence (IPMI) model to explore how media messages and interpersonal communication indirectly affect Chinese women's support for birth encouragement policies. Surveying 616 Chinese women of reproductive age, this study finds that exposure to media messages regarding childbirth benefits and interpersonal communication are positively correlated with the presumed influence of such media messages on others. Presumed media influence on others is further positively associated with perceived personal norms and social norms regarding support for birth encouragement policies. Perceived social and personal norms, in turn, are positively associated with Chinese women's support for birth encouragement policies. The theoretical and practical implications of this study are examined.